The use of maggot meal in African cat fish Feeding - Dudusola, Adetarami; S. Temenu , Akinlade (Advances in Aquaculture and Fisheries Management, 2013)
A twelve week feeding trial was carried out to evaluate the growth and nutrient utilization of African catfish (Clarias gariepinus) fingerlings fed varying levels of maggot meal. Maggot meal was produced from a mixture of 25 kg of cattle blood, 70% wheat bran, and 30% saw dust and substituted for fish meal in the fish diet to produce five varying levels of maggot meals- Treatment 1 (Trt 1) contained 0% of maggot meal (control), Trt 2 (50% maggot meal), Trt 3 (33.3% maggot meal), Trt 4 (66.6% maggot meal), and Trt 5 (75% maggot meal). A total of 150 fingerlings (two weeks old ±21.74 g) were allotted to five dietary treatments (fifteen fingerlings per tank) in a randomized design. Highest mean weight gain (MWG), percentage weight gain (PWG) and specific growth rate (SGR|) (35.47 g, 63.23%, 1.30%/day) were observed in Trt5 (75% maggot inclusion) respectively while the least values, 13.545 g, 62.29%, 0.69%/day were observed in Trt1 (control) respectively. In the same vein highest value of feed intake (116.4 kg) was recorded for Trt5 and least value (71.8 kg) was found with Trt3. However, FCR were significantly (P< 0.05) higher, Trt5 had the least FCR (3.13) and the highest value of 5.07 was found with fish fed control diet. Trt5 had the highest values of protein intake (PI) 47.60 and protein efficiency ratio (PER) 0.75, respectively. The results observed for FI showed that the feed were highly acceptable by the fish and the best growth response was achieved at higher level of maggot inclusion (75% maggot meal inclusion). Highest PER is also an indication that maximum utilisation of nutrients was obtained at the higher levels of maggot meal in the diet. Also, best of feed to flesh gain ratio was attained at the higher level of maggot inclusion. Therefore, it can be concluded that maggot meal can replace fish meal up to 75% without any adverse effect on the growth of the fish.